Individual and Relationship-Level Correlates of Transactional Sex Among Adolescent Girls and Young Women in Malawi: A Multilevel Analysis - Margaret W Gichane; Nora E Rosenberg; Catherine Zimmer; Audrey E Pettifor; Suzanne Maman; Bertha Maseko; Kathryn E Moracco (My University, 2022)
Transactional sex increases HIV risk among adolescent girls and young women (AGYW). Understanding the individual and dyadic nature of transactional sex may provide evidence for risk reduction interventions. Multilevel logistic regression was used to cross-sectionally examine correlates of transactional sex among AGYW in Lilongwe, Malawi. Participants (N = 920) reported 1227 relationships. Individual-level associations were found between being divorced/widowed (AOR 5.07, 95% CI 1.93, 13.25), married (AOR 0.26, 95% CI 0.09, 0.72), or unstably housed (AOR 7.11, 95% CI 2.74, 18.47) and transactional sex. At the relationship-level, transactional sex occurred in relationships with: non-primary primary partners (AOR 4.06, 95% CI 2.37, 6.94), perceived partner concurrency (AOR 1.85, 95% CI 1.11, 3.08), and feared violence with couples HIV testing (AOR 2.81, 95% CI 1.26, 6.29), and less likely to occur in relationships with children (AOR 0.15, 95% CI 0.06, 0.38). Multiple co-occurring social and structural vulnerabilities increase transactional sex engagement warranting the need for social protection and gender transformative approaches.
Keywords: Adolescent girls; Multilevel; Partners; Transactional sex; Young women.